IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE PARAGRAPH BY USING CONCEPT MAPPING AT CLASS X-1 TKJ OF SMK YOHANES XXIII MAUMERE IN 2016/2017 ACADEMIC YEAR - Yanti, Yuliana Agustina; Daming, Srinanengsi; Tanan, Yuliana; Syam, Ummu Haerah; Ufrawati, Ufrawati (La Ogi : English Language Journal, 2024)
This study aims to know whether concept mapping can improve the students’ ability in writing descriptive paragraph at class X-1 TKJ of SMK Yohanes XXIII Maumere. This study was conducted in SMK Yohanes XXIII in the 1st semester of the school year 2016-2017. The population of this study was 32 students who are all examined. This research used classroom action research which conducted in two cycles. Each cycles consisted of planning, action, observation and reflection. The instruments used are observations checklist, reflection notes, pre-test, post-test and questionnaire. The technique of analyzing data is collected through administering pre-test, post-test and questionnaire. The result of the data analysis of pre-test score showed the mean figure of 47.96. The result of the data analysis of post-test score in cycle 1 (S2) showed the increasing mean figure of 67.37. The result of data analysis of post-test score obtained by the subjects under in cycle 2 (S4) pointed out the increasing mean figure of 80.90. Comparing the mean figure of pre-test score, the mean figure obtained by the subjects under study for each cycle was convincingly much higher than the mean figure of pre-test score. These findings clearly showed that concept mapping could improve the students’ ability in writing descriptive paragraph. The result of the data analysis of questionnaire score in pre-test showed the comparative percentages figures of option A: in 7.67%, option B: 24.04%, option C: 68.28%, option D: 0%. The result of the data analysis of questionnaire score in cycle 1 showed the comparative percentages figure of option A: 5.95%, option B: 64.82%, option C: 45.05%, option D: 0%. The result of the data analysis of questionnaire score in cycle 2 showed the comparative percentages figure of option A: 77.19%, option B: 22.45%, option C: 0,35%, option D: 0%. The result comparative percentages figure clearly showed the subjects attitude and motivation in learning descriptive paragraph writing changed positively. Based on this findings, it can be concluded that the application of the concept mapping technique can improve students’ writing ability in class X-1 TKJ of SMK Yohanes XXIII Maumere in 2016/2017 academic year.